Linking Models and Experiments, Volume 2 Proceedings of the 29th IMAC, A Conference on Structural Dynamics, 2011 - Proulx, Tom.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Linking Models and Experiments, Volume 2. Proceedings of the 29th IMAC, A Conference and Exposition on Structural Dynamics, 2011, the second volume of six from the Conference, brings together 33 contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on Finite Element Techniques, Model Updating, Experimental Dynamics Substructuring, Model Validation, and Uncertainty Quantification.
Modal Testing and FE-model Validation of Azimuthing Thruster -- POD Based Computation of Joint Interface Modes -- Area Wise Application of Contact Constraints in Reduced Mechanical Systems -- On the Extension of Global Vibration Modes With Ritz-vectors Needed for Local Effects -- Direct Decoupling of Substructures Using Primal and Dual Formulation -- Spectral Analysis of Vibrating Plates With General Shape -- Smoothing Experimental Data in Dynamic Substructuring of Built up Systems -- Metrics for Diagnosing Negative Mass and Stiffness When Uncoupling Experimental and Analytical Substructures -- Propagation of Free-interface Substructure Uncertainty into System Test-analysis Correlation -- Feature Extraction for Structural Dynamics Model Validation -- Hybrid Sets of Merged Data for Modal Model Applications -- Dynamic Uncoupling of a System Model for Component Identification -- Full Field Dynamic Stress/Strain From Limited Sets of Measured Data -- Limited Experimental Displacement Data Used for obtaining Full-field Dynamic Stress Strain Information -- A Survey of Techniques to Estimate the Uncertainty in Material Parameters -- Construction of DEM-base Traffic Model Using Optimal Velocity Model -- Confidence Intervals of Modal Parameters During Progressive Damage Test -- Identification of Material Properties of Composite Plates Utilizing Model Updating and Response Surface Techniques -- Globally Enriched Substructuring Techniques for Vibro-acoustic Simulation -- A Modal-geometrical Selection Criterion for Master Nodes: Numerical and Experimental Testing -- Robust Optimization and Quality Control in Spot Welded Structures -- Interface Reduction in the Dual Craig-Bampton Method Based on Dual Interface Modes -- A Truly Hybrid Approach to Substructuring Problems Using Mixed Assembly and Implicit Solving Strategies -- Model Updating Methodologies for Multibody Simulation Models: Application to a Full-scale Wind Turbine Model -- DOF Reduction Strategy for Large Order Finite Element Models -- Understanding Large Order Finite Element Model Dynamic Characteristics -- FEM Sensitivity Method for Uncertainty and Reconciliation Analyses -- Uncoupling Techniques for the Dynamic Characterization of Sub-structures -- Receptance Based Normalization of Operational Mode Shapes -- Fault Simulation in a Gearbox Using Finite Element Model Reduction Techniques -- Response Measurements of DMS Cabinets and Supporting Truss Structures Under Environmental and Transient Wind Loads -- Variance Decomposition in the Presence of Epistemic and Aleatory Uncertainty -- A Forecasting Metric for Predictive Modeling.
Keywords: Engineering; Engineering mathematics; Mechanical engineering; Astronautics; Engineering; Appl.Mathematics/Computational Methods of Engineering; Aerospace Technology and Astronautics; Structural Mechanics